2021
DOI: 10.3390/sym13101920
|View full text |Cite
|
Sign up to set email alerts
|

Tendencies in ABO3 Perovskite and SrF2, BaF2 and CaF2 Bulk and Surface F-Center Ab Initio Computations at High Symmetry Cubic Structure

Abstract: We computed the atomic shift sizes of the closest adjacent atoms adjoining the (001) surface F-center at ABO3 perovskites. They are significantly larger than the atomic shift sizes of the closest adjacent atoms adjoining the bulk F-center. In the ABO3 perovskite matrixes, the electron charge is significantly stronger confined in the interior of the bulk oxygen vacancy than in the interior of the (001) surface oxygen vacancy. The formation energy of the oxygen vacancy on the (001) surface is smaller than in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 92 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…For eigenvalues smearing a 0.02 eV Gaussians of width was chosen. As its well-known that the hybrid exchange-correlation functionals, like B3LYP or B3PW allow to achieve an excellent agreement with the experimental calculations for the band gaps of different materials, [42][43][44][45] whereas the DFTbased methods (eg, GGA, PBE), as a rule underestimate the band gap of those materials [46][47][48][49][50][51] ; Hence, we applied HSE and PBE functionals individually for intrinsic band structure calculations in order to determine band gap oscillation; It was observed that, there is no such bigger fluctuation in band gap values of both functionals for given systems, and a minute variation of $0.04 eV is observed in the energy gaps.…”
Section: Methodsmentioning
confidence: 99%
“…For eigenvalues smearing a 0.02 eV Gaussians of width was chosen. As its well-known that the hybrid exchange-correlation functionals, like B3LYP or B3PW allow to achieve an excellent agreement with the experimental calculations for the band gaps of different materials, [42][43][44][45] whereas the DFTbased methods (eg, GGA, PBE), as a rule underestimate the band gap of those materials [46][47][48][49][50][51] ; Hence, we applied HSE and PBE functionals individually for intrinsic band structure calculations in order to determine band gap oscillation; It was observed that, there is no such bigger fluctuation in band gap values of both functionals for given systems, and a minute variation of $0.04 eV is observed in the energy gaps.…”
Section: Methodsmentioning
confidence: 99%
“…All calculations are based on the first-principles calculations implemented in the Vienna ab initio Simulation Package (VASP) code [ 17 , 18 ] in the framework of the density functional theory (DFT). To solve the Kohn–Sham equations, the generalized gradient approximation (GGA) within the Perdew–Burke–Ernzerhof (PBE) formulation [ 19 ] or the B3LYP(B3PW) [ 20 , 21 ] is widely used to describe exchange-correlation potential. In this study, we used the former method to describe the exchange-correlation potential.…”
Section: Theoretical Methods and Computational Detailsmentioning
confidence: 99%
“…Since the oxygen composition plays a significant role in the phase transition in many material systems, some attempts were executed based on the ab initio calculations to research the formation of oxygen vacancies in the perovskite structure. 9,10 It is worth noting that pronounced MIT and magnetic transitions were usually achieved at x values of ∼2/3 in Re 1−x Sr x FeO 3 with light rare-earth compositions (e.g., La, Pr, and Nd). This was attributed to the charge ordering (CO) in the Fe site following a Fe 3+ -Fe 3+ -Fe 5+ sequence along the <111> axis direction when descending the temperature across a critical point (T CO ) that opens the energy band gap abruptly.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, the MIT behaviors were observed in both the high-valence Fe-associated oxides, such as AFeO 3 (A represents alkane earth, e.g., Ca or Ca 1– x Sr x ), Re Cu 3 Fe 4 O 12 ( Re represents rare earth), , and ( Re ,A)­FeO 3 , and the low-valence Fe-containing oxides, such as Fe 3 O 4 , Re BaFe 2 O 5 , and Re Fe 2 O 4 . , Taken ( Re ,A)­FeO 3 as a representative example, the valence state of Fe can be well controlled by either adjusting the Re /A ratio or the oxygen composition, and this further results in dramatic changes in their crystal and electronic structures as well as electric/magnetic properties. Since the oxygen composition plays a significant role in the phase transition in many material systems, some attempts were executed based on the ab initio calculations to research the formation of oxygen vacancies in the perovskite structure. , It is worth noting that pronounced MIT and magnetic transitions were usually achieved at x values of ∼2/3 in Re 1– x Sr x FeO 3 with light rare-earth compositions (e.g., La, Pr, and Nd). This was attributed to the charge ordering (CO) in the Fe site following a Fe 3+ -Fe 3+ -Fe 5+ sequence along the <111> axis direction when descending the temperature across a critical point ( T CO ) that opens the energy band gap abruptly .…”
Section: Introductionmentioning
confidence: 99%